Dependence analysis for inferring information flow properties in Spark ADA programs - Thiagarajan, Hariharan (Kansas State University, 2011)
With the increase in development of safety and security critical systems, it is important to have more sophisticated methods for engineering such systems. It can be difficult to understand and verify critical properties of these systems because of their ever growing size and complexity. Even a small error in a complex system may result in casualty or significant monetary loss. Consequently, there is a rise in the demand for scalable and accurate techniques to enable faster development and verification of high assurance systems. This thesis focuses on discovering dependencies between various parts of a system and leveraging that knowledge to infer information flow properties and to verify security policies specified for the system. The primary contribution of this thesis is a technique to build dependence graphs for languages which feature abstraction and refinement. Inter-procedural slicing and inter-procedural chopping are the techniques used to analyze the properties of the system statically. The approach outlined in this thesis provides a domain-specific language to query the information flow properties and to specify security policies for a critical system. The spec- ified policies can then be verified using existing static analysis techniques. All the above contributions are integrated with a development environment used to develop the critical system. The resulting software development tool helps programmers develop, infer, and verify safety and security systems in a single unified environment.
Keywords: Information flow; Dependence graph; Policy language; Specification and verification; Computer Science (0984)